2017
DOI: 10.3390/v9010022
|View full text |Cite
|
Sign up to set email alerts
|

Astrovirus Pathogenesis

Abstract: Astroviruses are a major cause of diarrhea in the young, elderly, and the immunocompromised. Since the discovery of human astrovirus type 1 (HAstV-1) in 1975, the family Astroviridae has expanded to include two more human clades and numerous mammalian and avian-specific genotypes. Despite this, there is still little known about pathogenesis. The following review highlights the current knowledge of astrovirus pathogenesis, and outlines the critical steps needed to further astrovirus research, including the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 81 publications
4
82
0
1
Order By: Relevance
“…The AstV*age interaction was significant in the models. In Jamaican fruit bats as well as in other studies on bats [31] and humans [3] the AstV prevalence was found to be higher in young individuals. More research including experimental AstV-infection of individuals with healthy and dysbiotic microbiomes can help to proof such cause-and-effect relationships.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The AstV*age interaction was significant in the models. In Jamaican fruit bats as well as in other studies on bats [31] and humans [3] the AstV prevalence was found to be higher in young individuals. More research including experimental AstV-infection of individuals with healthy and dysbiotic microbiomes can help to proof such cause-and-effect relationships.…”
Section: Discussionsupporting
confidence: 56%
“…Astroviruses are a major cause of diarrhoea in children [1]. Interestingly, -and in contrast to strong health effects they have in humans-some wildlife species, including bats, remain phenotypically asymptomatic after infection [3]. However, disease symptoms after AstV-infection may only be less visible in bats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations